40 Years of Cracking the Orthographic Code: A Special Issue in Honour of Jonathan Grainger’s Career - Joshua Snell; Sebastiaan Mathôt; Mathieu Declerck (Journal of Cognition)
Anyone recounting the history of cognitive psychology will have to make early mention of the study of orthographic processing (starting in 1886 with the seminal work of Cattell, a doctoral student of Wilhelm Wundt); and anyone recounting the study of orthographic processing will have to make mention of Jonathan Grainger. An honorary member and former president of the European Society for Cognitive Psychology, Jonathan has dedicated nearly four decades of research to the mechanisms driving the recognition of letters, words and sentences during reading. In honour of Jonathan’s career—which formally has come to a close in 2023—in this Special Issue several contemporaries and close collaborators highlight important advances that have been made in the past 40 years, and provide flavours of where the field stands today.